Market and Entrepreneurial Orientation Affect Marketing Performance in Small and Medium-Sized Businesses Through Competitive Advantage - Masuku, Djunaid; Jannang, Abdul Rahman; Haji, Sulfi Abdul (Pusat Penerbitan dan Publikasi Ilmiah, FEB, Universitas Muslim Indonesia, 2023)
This study examines the effect of market orientation and entrepreneurial orientation on marketing performance in SMEs in Ternate City. It uses explanatory research to analyze the cause-and-effect relationship between variables and test hypotheses. The sample consisted of 85 respondents from the food sector, selected using proportional stratified random sampling. Data analysis was conducted through path analysis using SmartPLS version 4.0. The results showed that market orientation, entrepreneurial orientation, competitive advantage, and marketing performance have a significant influence. However, market orientation does not directly impact marketing performance, especially through competitive advantage. This study suggests the need for increased market orientation activities to improve marketing performance. This can be achieved by understanding consumer preferences, monitoring competitor products, and improving organizational structure. By implementing these strategies, SMEs in Ternate City can achieve better competition and marketing performance.